GAPS IDENTIFICATION OF INCLUSIVE EDUCATION: EVALUATIVE STUDY AT MADRASAH IBTIDAIYAH MA'ARIF SIDOMULYO, KEBUMEN - Wahid Khozin; Opik Abdurrahman Taufik (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
AbstractThis study was evaluating the Ministry of Religion Affairs’ policy intending to provide input for improving the program. The evaluation took the case in Madrasah Ibtidaiyah (MI) Ma'arif in Ambal, Kebumen, Central Java. This MI uses the concept of inclusive education that sees every child entitled to educational services regardless of their physical differences and who they are. At the level of implementation, there is still a gap between a theory that tends to be ideal with practices that emphasize real needs. To meet the educational services of children with disabilities in their environment, MI Ma'arif Sidomulyo chose to go directly and practice. To overcome obstacles in the field, MI initiated the building of networks with local governments, schools, and madrassas that provide inclusive education. The network was also built with institutions and observers of inclusive education as an effort to strengthen inclusive education in MI Sidomulyo, because guidance from the Ministry of Religion is still very weak.AbstrakKajian ini mengevaluasi kebijakan Kementerian Agama yang hendak memberikan masukan untuk perbaikan program. Evaluasi mengambil kasus di Madrasah Ibtidaiyah (MI) Ma'arif di Ambal, Kebumen, Jawa Tengah. MI ini menggunakan konsep pendidikan inklusif yang memandang setiap anak berhak atas layanan pendidikan tanpa memandang perbedaan fisik dan siapa mereka. Pada tataran implementasi, masih terdapat gap antara teori yang cenderung ideal dengan praktik yang menekankan pada kebutuhan nyata. Untuk memenuhi layanan pendidikan anak difabel di lingkungannya, MI Ma'arif Sidomulyo memilih terjun langsung dan praktek. Untuk mengatasi kendala di lapangan, MI memprakarsai pembangunan jejaring dengan pemerintah daerah, sekolah, dan madrasah penyelenggara pendidikan inklusif. Jejaring juga dibangun dengan lembaga dan pemerhati pendidikan inklusif sebagai upaya penguatan pendidikan inklusif di MI Sidomulyo, karena pembinaan dari Kementerian Agama masih sangat lemah.